Jerusalem Pilgrims: Spirituality, Rationality, and the Iconic in the Ministry of St. George’s College - Need, Stephen W. (The international journal of religion and spirituality in society, 2022)
Pilgrims to Jerusalem and the Holy Land often find questions about the authenticity of holy places unsettling. But genuine questions lead to new horizons. The Anglican St. George’s College in Jerusalem offers holistic "study-pilgrimages," which bring prayer and devotion together with academic study. Following the hermeneutics of Hans-Georg Gadamer, the interplay between the spiritual and the rational on a pilgrimage is characterized here as a "conversation" and imagined as an element within a personal relation with the divine as understood by Martin Buber. These ideas are explored further through a consideration of the classical theology of icons found in the writings of John of Damascus and Theodore the Studite in the eighth and ninth centuries, and rooted in the Christology of the Council of Chalcedon (451 CE). Overall, pilgrimage and holy places are seen as "iconic" and the conversation between the spiritual and the rational as having its roots in the relational interplay between the human and the divine. It is maintained that spirituality and rationality can co-exist on St. George’s College courses within a creative inter-relation which draws pilgrims into the presence of God, showing that questions of the authenticity of sites are only part of a much wider pilgrim experience.